2020
DOI: 10.1101/2020.06.30.176537
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attenuated Subcomponent Vaccine Design Targeting the SARS-CoV-2 Nucleocapsid Phosphoprotein RNA Binding Domain:In silicoanalysis

Abstract: ABSTRACTThe novel coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has previously never been identified with humans, thereby creating devastation in public health. The need for an effective vaccine to curb this pandemic cannot be overemphasized. In view of this, we, therefore, designed a subcomponent antigenic peptide vaccine targeting the N-terminal (NT) and C-terminal (CT) RNA binding domains of nucleocapsid protein that ai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…3). The only 3D model with more than 70% of its residues in the favored region is deemed a quality structure (Chukwudozie et al, 2020).…”
Section: Tertiary Structure Development Refinement and Validationmentioning
confidence: 99%
“…3). The only 3D model with more than 70% of its residues in the favored region is deemed a quality structure (Chukwudozie et al, 2020).…”
Section: Tertiary Structure Development Refinement and Validationmentioning
confidence: 99%
“…Chukwudozie et al 6,34 have extensively provided a comprehensive and simplified step in designing peptide vaccines and also provided various approaches in validating them using in silico checkpoints. The steps involved in designing an epitopic peptide vaccine adopting immuno-informatics method include proteomic data retrieval of the protein of interest and adoption of computational immunology analysis of the data, which includes test for antigenicity, allergenicity, peptide toxicity, and epitopic conservancy.…”
Section: Steps Involved In Immuno-informaticsmentioning
confidence: 99%
“…Other quality checks such as their respective antigenicity, allergenicity, peptide toxicity, and peptide conservancy, which characterize their immunogenicity profile, are considered. A well-summarized and applied process of these steps can be seen in a study conducted by Chukwudozie et al 6,34…”
Section: Processmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Chukwudozie et al developed a subcomponent vaccine targeting the SARS-CoV-2 nucleocapsid phosphoprotein RNA binding domain. This vaccine contains both antigenic B cell and T cell epitopes that provide a sufficient antigenic index and nonallergenic property [8]. Importantly, Peng et al revealed that CD8+ T cell responses were associated with milder disease (2-3 weeks recovery rates), whereas more severe cases of SARS-CoV-2 had lower CD8+ T cell responses.…”
Section: Introductionmentioning
confidence: 99%